Dr. Disaster's guide to surviving everything : essential advice for any situation life throws your way - Torres, John E. (New York, NY : HarperCollins Publishers, 2021)
"A practical, all-encompassing guide to disaster preparedness-from avalanches and blackouts to pandemics and wildfires-from NBC News senior medical correspondent and emergency medicine physician Dr. John Torres"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: First aid in illness and injury -- Popular works; Emergency management -- Popular works; Survival -- Popular works